2014
DOI: 10.2304/plat.2014.13.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Teach Reading: A Theory-Practice Approach to Psychology Teaching in University Teacher Education

Abstract: The report portrays a theory-practice psychology course on reading education in a German teacher education programme. Having completed a theoretical course phase that is largely based on knowledge from cognitive and educational psychology, pre-service student-teachers applied their acquired knowledge by working with a fifth-grader in five individual reading lessons. During the sessions, students were supported by a mentor and received individual video feedback as well as peer feedback. The students also kept a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…We conclude that the RT students found the program useful and practicable for fostering reading skills as the majority of them gave the highest social validity ratings. Whereas research by Drechsel et al. (2014) indicated that teaching university students how to teach reading strategies can be useful for one-on-one tutoring, our research took this a step further by providing students with the competence to teach a scientifically based reading instruction program to an entire class in regular lessons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that the RT students found the program useful and practicable for fostering reading skills as the majority of them gave the highest social validity ratings. Whereas research by Drechsel et al. (2014) indicated that teaching university students how to teach reading strategies can be useful for one-on-one tutoring, our research took this a step further by providing students with the competence to teach a scientifically based reading instruction program to an entire class in regular lessons.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Drechsel, Breuning, Thurn, and Basten (2014) instructed university students in teaching fifth graders how to learn from texts. Within this study, the students had the opportunity to teach reading strategies to fifth graders in individual lessons.…”
Section: Learning How To Teach Reading Strategiesmentioning
confidence: 99%
“…Having concrete teaching experiences is an emphasized aspect for psychological training for student teachers. They are advised to be educated with a theory-practice approach with the help of mentor feedback and keeping journals for reflective purposes in order to lessen reality shock they experience, help them build a bridge between theory and practice, and prepare them psychologically for the complexities of real classroom settings (Drechsel, Breunig, Thurn, & Basten, 2014).…”
Section: ______________________________________________mentioning
confidence: 99%
“…Based on the existing literature, it can be claimed that a growing body of research has contributed to the understanding of psychology in terms of teacher identity (Brown, 2006;Friesen & Besley, 2013), teacher induction (Evelein, Korthagen, & Brekelmans, 2008;Tomlinson, 2008;Drechsel, Breunig, Thurn, & Basten, 2014), teacher beliefs (Smylie, 1988), psychoeducational assessment (Harris & Joy, 2010), teacher burnout (Singh & Billingsley, 1996;Gold & Roth, 2005;Bartholomew, Ntoumanis, Cuevas, & Lonsdale, 2014;Alkhateeb, Kraishan & Salah, 2015;De Neve & Devos, 2016), stakeholder involvement (Lee & Nie, 2014;Sağnak, Kuruoz, Polat, & Soylu, 2015;Pur, Liman, & Ali, 2016), psychological capital (Bissessar, 2014), psychological resilience (YokuĢ, 2015), classroom management (Seiz, Voss, & Kunter, 2015), psychological intervention (Maralani, Lavasani, & Hejazi, 2016) and psychodiagnostic activities (Minakhmetova & Pyanova, 2016).…”
Section: ______________________________________________mentioning
confidence: 99%
See 1 more Smart Citation